1999
DOI: 10.1001/archinte.159.14.1550
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis After Community-Acquired Pneumonia in the Elderly

Abstract: The present results indicate that elderly patients treated for CAP are at high risk of subsequent mortality for several years. Based on the high incidence and negative long-term effects of pneumonia, it can be concluded that there is a clear need for prevention, eg, by influenza and pneumococcal immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
5
15

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 43 publications
7
105
5
15
Order By: Relevance
“…However, long-term mortality remained poor in our cohort, as shown in other studies. 14 Age is considered a major predictor of poor outcome in many illnesses, including pneumonia, and is an important component of the PPI risk classification system. In our study, almost half of the episodes designated Class 3 and Class 4 did not have any PPI-specific comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term mortality remained poor in our cohort, as shown in other studies. 14 Age is considered a major predictor of poor outcome in many illnesses, including pneumonia, and is an important component of the PPI risk classification system. In our study, almost half of the episodes designated Class 3 and Class 4 did not have any PPI-specific comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…25 A study with 12-year follow-up after CAP demonstrated a relative risk for pneumonia-related mortality of 2.1 and a relative risk for overall mortality of 1.5. 26 We suspect that a large proportion of late deaths in our cohort was due to respiratory disorders such as pneumonia, but we did not determine the cause of death for those who died after hospitalization or completion of outpatient treatment. Clinicians who treat persons with SCI should be aware that those who survive CAP are at high risk for mortality in subsequent years.…”
Section: Discussionmentioning
confidence: 99%
“…A diferencia de otros autores [15][16][17][18][19][20][21] , no observamos diferencias significativas en la sobrevida a largo plazo entre en una cohorte de pacientes adultos mayores de 60 años hospitalizados por neumonía comunitaria y un grupo control hospitalizado por otra condición médica (Figura 1). Esta discordancia puede ser atribuida a múltiples causas: características de la población examinada, diseño metodológico, tamaño muestral, análisis estadístico y período de seguimiento de los diferentes estudios.…”
Section: Artículos De Investigaciónunclassified
“…Aunque la resolución clínica a los 30 días ha sido empleada tradicionalmente como un indicador de la supervivencia de los pacientes con NAC, estudios recientes sugieren que la neumonía puede influir en el pronóstico de los enfermos y la supervivencia a largo plazo [13][14][15][16][17][18][19][20][21] . Los estudios que han demostrado una disminución en la sobrevida a largo plazo después de la hospitalización en pacientes con NAC han utilizado diferentes diseños metodológicos y análisis estadísticos.…”
unclassified
See 1 more Smart Citation